Using physlets in undergradute physics: a solving tool - Ahmad Puaad Othman, (Universiti Kebangsaan Malaysia, 2004)
Computer simulations is now becoming a common feature in many undergraduate physics textbook together with online supplements to supposedly enhance learning and understanding. Many questions arise as to how these computer simulations and online supplements are developed and is it a worthy investment on the part of the physics educators. In this paper we look at the ways how "Physlets" (Physics Applets) are developed for the purpose of the undergraduate physics curriculum. JAVA is the fastest-growing programming language today. In scientific programming, the JAVA language meets the need for a simpler object-oriented language than C++ but is not yet popular, useful and widely used in very large scale or number crunching physics simulations. One of JAVA applets’s strength is that it is device independent. And for physics learning, simulation applets embedded in World Wide Web pages allow interactive learning and students-programmable demonstrations. We will examine a few physics simulations using JAVA applets that we have developed. We also discuss the various different aspects of using JAVA applets in developing physics simulation. And finally we will look into the reasons as to why it is still not ready for use in intensive physics simulation.